Research note on eco-efficient supply chain integration - Latifah Naina, Mohamed; Fernando, Yudi (KnE Social Sciences, 2019)
Manufacturing must strictly improve environmental protection as this will able to triggers eco-efficient based innovation. At the same time, it will lead manufacturing to achieve the optimum level of environment protection and improve business performance. Currently, environmental improvement still a lack of pressure given for industry to implement environmentally friendly management practices even though the improvements in energy efficiency are obvious. Eco-efficiency has been expanded through green and lean initiatives; there is a decline in the level of integration for eco-efficiency in the supply chain to balance in both environmental and economic aspects. Thus, the objective of this study is to determine the impact of eco-efficient supply chain integration in environmental manufacturing protection improvement. The paper elaborates the importance of eco-efficient supply chain integration in environmental manufacturing protection to indicate of their improvement. The application and mechanics of eco-efficient supply chain integration discussed related to the implementation of the current practices of environmental manufacturing protection improvement.